6-Shogaol Abrogates Parkinson's Disease in Rotenone-Induced Rodents: Based on In Silico Study and Inhibiting TNF-α/NF-κB/IL-1β/MAO-B - Misbahuddin Rafeeq; Fahad A. Al-Abbasi; Muhammad Afzal; Ehssan Moglad; Salwa D. Al-Qahtani; Sami I. Alzrea; Naif A. R. Almalki; Faisal Imam; Nadeem Sayyed; Imran Kazmi (MDPI AG, 2024)
Background/Objectives: 6-Shogaol is a comparatively innovative anti-Parkinson's remedy with antioxidant and anti-inflammatory characteristics. This investigation intended to determine the role of 6-shogaol in the Parkinson's disease (PD) paradigm in rotenone-induced rats. Methods: Thirty male Wistar rats (10-12 weeks old; 180 ± 20 g) were divided into five groups. Animals with rotenone-induced experimental PD were subsequently treated with 6-shogaol-10 at 20 mg/kg for 28 days. After the experimental duration, behavioural investigations were performed, i.e., open field test, forced swim test, rotarod test, and catalepsy test. Biochemical assessments like AChE, GSH, CAT, SOD, MDA, nitrite, ceruloplasmin, proinflammatory markers such as IL-1β, NF-κB, TNF-α, and catecholamines markers (DA, GABA, and MAO-B) were determined. The docking procedure was conducted using the AutoDock Vina docking protocol. Furthermore, histopathology was performed. Results: Rotenone significantly increased the level of MAO-B, oxidative, nitrative, and pro-inflammatory markers. However, there was a decline in ceruloplasmin, dopamine, and endogenous antioxidants. Treatment with 6-shogaol (10 and 20 mg/kg) considerably sustained the elevation of oxidative stress and inflammatory indicators and decreased AChE activity and dopamine levels. In the histology of the brain, 6-shogaol improved the neuronal structure and reduced the degeneration of neurons. Based on the binding energy values, compound 6-shogaol demonstrates a favourable binding affinity to AChE, MAO-B, DA, and GABA with respective binding energies of −8.214, −8.133, −7.396 and −6.189 kcal/mol. Conclusions: In this study, 6-shogaol exhibited neuroprotective properties against PD, which could be employed as a prospective medication for PD.